Complete urological evaluation including sperm DNA fragmentation in male systemic lupus erythematosus patients. (January 2019) - Tiseo, BC; Bonfá, E.; Borba, EF.; Munhoz, GA.; Wood, GJA.; Srougi, M.; Silva, CA.; Cocuzza, M.
Objective: To evaluate sperm DNA fragmentation analysis in non-azoospermic male systemic lupus erythematosus (SLE) patients. Methods: Twenty-eight consecutive male SLE patients (American College of Rheumatology criteria) and 34 healthy controls were evaluated for demographic/exposures data, urological evaluation, hormone profile and sperm analysis (including sperm DNA fragmentation). Clinical features, disease activity/damage scores and treatment were also evaluated. Results: The median age (33 (20–52) vs. 36.5 (25–54) years, P  = 0.329) and frequency of varicocele (25% vs. 32%, P  = 0.183) were similar in SLE patients and healthy controls. Sperm DNA fragmentation showed significantly higher levels of cells class III (44 (9–88) vs. 16.5 (0–80)%, P  = 0.001) and cell class IV (10.5 (3–86) vs. 7 (0–36)%, P  = 0.039) in SLE. The sperm DNA fragmentation index was also significantly higher in SLE patients (62 (31–97) vs. 25.5 (0–100)%, P  < 0.001). Conventional sperm parameters (including sperm count, motility and morphology) were similar in both groups. In SLE patients no correlations were observed between sperm DNA fragmentation index and age, disease duration, Systemic Lupus Erythematosus Disease Activity Index 2000 and Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index scores, and cumulative dose of prednisone, hydroxychloroquine, intravenous cyclophosphamide, methotrexate, azathioprine and mycophenolate mofetil ( P  > 0.05). Further analysis of SLE patients treated with and without intravenous cyclophosphamide showed that total sperm motility was significantly lower in the former group (64% (15–83) vs. 72% (57–86), P  = 0.024). The sperm DNA fragmentation index was alike in both groups (52.5 (31–95) vs. 67.5 (34–97)%, P  = 0.185). Conclusions: To our knowledge, this is the first demonstration that male non-azoospermic SLE patients have increased sperm DNA fragmentation without evident gonadal dysfunction. Intravenous cyclophosphamide does not seem to be a major determinant for this abnormality. Future prospective study is necessary to determine the impact of this alteration in these patients' fertility.